Minority report [videorecording (Blu-Ray)] - Spielberg, Steven, 1946-; Cruise, Tom, 1962-; Farrell, Colin, 1976-; Morton, Samantha; Sydow, Max von, 1929-2020; Williams, John, 1932-; Dick, Philip K. (Paramount Home Entertainment, 2010)
John Anderton is a Washington D.C. detective in the year 2054. He is part of 'Precrime, ' a special police department that arrests criminals before they commit the actual crime. When Anderton discovers that he has been identified as a future killer, he must find out why and how he broke the law in order to prove his innocence of the crime he has yet to commit.